2018
DOI: 10.11591/ijece.v8i5.pp3057-3066
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Factor Effecting the Buying Judgement of Smart Phone

Abstract: <p>Smart phone has various utilizations to various clients as per their necessities. With sensational rise in the usage of smart phone the individuals are considering different factors while purchasing a smart phone. This paper has put endeavor to reveal the fundamental factors which effect clients in picking up of the smart phone. A sample of 512 responses was taken through questionnaire. An organized questionnaire was planned with five point Likert scale was utilized to meeting respondent’s .Factor ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Filieri and Lin [38] Qualitative face-to-face interview and Partial Least Square-Based Structural Equation Modeling Bhalla and Jain [40] Factor Analysis and Descriptive Analysis Laohakosol and Sharma [41] Correlation and Logistics Regression Bringula et al [42] Hierarchical Regression Analysis Martins et al [45] Partial Least Square-Based Structural Equation Modeling Redda and Shezi [44] Descriptive Analysis and Logistics Regression Isa et al [46] Partial Least Square-Based Structural Equation Modeling Mishra et al [22] IFS-MABAC Kim et al [47] Mixed Logit Mao et al [48] Partial Least Square-Based Structural Equation Modeling Sawaftah et al [49] Multiple Linear Regression and Analysis of Variance…”
Section: Contributor(s) Methodology Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Filieri and Lin [38] Qualitative face-to-face interview and Partial Least Square-Based Structural Equation Modeling Bhalla and Jain [40] Factor Analysis and Descriptive Analysis Laohakosol and Sharma [41] Correlation and Logistics Regression Bringula et al [42] Hierarchical Regression Analysis Martins et al [45] Partial Least Square-Based Structural Equation Modeling Redda and Shezi [44] Descriptive Analysis and Logistics Regression Isa et al [46] Partial Least Square-Based Structural Equation Modeling Mishra et al [22] IFS-MABAC Kim et al [47] Mixed Logit Mao et al [48] Partial Least Square-Based Structural Equation Modeling Sawaftah et al [49] Multiple Linear Regression and Analysis of Variance…”
Section: Contributor(s) Methodology Usedmentioning
confidence: 99%
“…Shieh and Lai [39] understood the importance of brand experience in establishing the brand loyalty among the consumers. Bhalla and Jain [40] reported the influence of the demographic variables on consumers' choices, and the physical attributes and features were major influences, followed by brand, price, serviceability, and social status. Exploring the influencing factors affecting the selection of smartphones in Nepal, Laohakosol and Sharma [41] concluded that their compatibility to various platforms and apps, the features of the product, and social pressure are given more importance by the consumers.…”
Section: Smartphone Selectionmentioning
confidence: 99%
“…Calisir used [20] Morlet Wavelet Support vector machine along with Linear discriminant analysis for diabetes classification. Their achieved classification accuracy of 89.74%.For classification one of supervised powerful techniques naïve bayes can also be used for prediction of diabetes.Naive bayes already used for prediction of mobile phone [21]. Other powerful data mining algorithms have been used for prediction of hear diseases [22].…”
Section: Related Workmentioning
confidence: 99%
“…Thus, in the measurement of user satisfaction, there are five variables measured, that is content, accuracy, format, ease of use, and timeliness [23]. We also used a five-level Likert scale as in [24]. The calculation result of the average percentage score of each variable in the satisfaction test of WSM method implementation in UMN Bulletin application for recommendation of information based on student interest shown in Table 3.…”
Section: System Evaluationmentioning
confidence: 99%